2010
DOI: 10.1108/17511871011061073
|View full text |Cite
|
Sign up to set email alerts
|

Patients' satisfaction with the bulk trolley system in a government hospital in Malaysia

Abstract: The purpose of this paper is to determine patients' satisfaction with the bulk trolley food service system and the effect of the system on energy and protein intakes. Design/methodology/approach: An interview-based questionnaire was used to measure patients' satisfaction (n = 70) with the hospital food services. Dietary intake of hospital food was determined through one-day weighed food intake survey and a food record for nonhospital food. Findings: The majority of the patients (98.6 per cent) were satisfied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Meal delivery systems play an essential role in monitoring and assessing patients' food intake. Inpatients preferred the trolley system over the pre-plated meal system because the temperature was more controlled [56][57][58]. However, one study compared Bistro-style meals and pre-plated services and reported no significant differences in the patients' food intake, satisfaction, and meal quality [34].…”
Section: Discussionmentioning
confidence: 99%
“…Meal delivery systems play an essential role in monitoring and assessing patients' food intake. Inpatients preferred the trolley system over the pre-plated meal system because the temperature was more controlled [56][57][58]. However, one study compared Bistro-style meals and pre-plated services and reported no significant differences in the patients' food intake, satisfaction, and meal quality [34].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study conducted in Malaysia to evaluate patients' satisfaction with the bulk trolley system and the energy and protein discovered that while most patients were satisfied with the foodservice, the majority did not meet their total energy and protein requirements from the hospital food provided. The purpose of distributing food via the bulk trolley service were to improve the quality of food by retaining temperature and allow patients to make selections at the point of service regarding the type of dish, portion size and amount of gravy (32).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is insufficient information in the questionnaire designed for the Malaysian population. It is challenging to use the instrument in measuring food preferences due to differences in food culture and practices, which are linked to multi-ethnicity and diverse religions and socio-demographic backgrounds (17). Thus, this study aims to develop and validate a measurement tool using the TQM approach for monitoring and evaluating hospital food service operations.…”
Section: Introductionmentioning
confidence: 99%